Using evidence to drive action: A "revolution in accountability" to implement quality care for better maternal and newborn health in Africa. Issue 1 (18th July 2014) - Hulton, Louise; Matthews, Zoe; Martin‐Hilber, Adriane; Adanu, Richard; Ferla, Craig; Getachew, Atnafu; Makwenda, Charles; Segun, Babatunde; Yilla, Mohamed
Abstract: Introducing evidence‐based accountability mechanisms at national and subnational levels into maternal newborn health programs can accelerate reductions in maternal and newborn mortality. Clearly packaged evidence has the potential to catalyze change, if it is communicated not only to the public but also to key policymakers. Evidence for Action (E4A) is a DFID‐funded program that contributes to global efforts toward improving accountability in maternal and neonatal health. It uses evidence to drive action and accountability to improve maternal and newborn survival in six African countries: Ethiopia, Ghana, Malawi, Nigeria, Sierra Leone, and Tanzania. This paper introduces the E4A program, the rationale that underpins the program design, and presents initial findings on how information and data currently feed into accountability and implementation across the six E4A countries.